7q11.23 Microduplication: a recognizable phenotype. (8th April 2012) - Dixit, A; McKee, S; Mansour, S; Mehta, SG; Tanteles, GA; Anastasiadou, V; Patsalis, PC; Martin, K; McCullough, S; Suri, M; Sarkar, A
<x xml:space="preserve">Abstract</x> Dixit A, McKee S, Mansour S, Mehta SG, Tanteles GA, Anastasiadou V, Patsalis PC, Martin K, McCullough S, Suri M, Sarkar A. 7q11.23 Microduplication: a recognizable phenotype. Williams‐Beuren syndrome is a well‐known microdeletion syndrome with a recognizable clinical phenotype. The subtle phenotype of the reciprocal microduplication of the Williams‐Beuren critical region has been described recently. We report seven further patients, and a transmitting parent, with 7q11.23 microduplication. All our patients had speech delay, autistic features and facial dysmorphism consistent with the published literature. We conclude that the presence of specific dysmorphic features, including straight, neat eyebrows, thin lips and a short philtrum, in our patients with speech delay and autistic features provides further evidence that the children with 7q11.23 microduplication have a recognizable phenotype.